THE STRATEGY OF SMALL AND MEDIUM ENTERPRISES (SMEs) IN UPGRADING SOCIAL MEDIA MARKETING TO CONTENT MARKETING - Gunardi, Gunardi; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2020)
The era of the internet is moving and developing very fast. The use of social media that had only been used to communicate and socialize turned into a marketing campaign tool. On the other hand, the use of the internet to develop content can also be used as a marketing campaign tool and is known as content marketing. It will be seen how social media marketing is also related to content marketing. The resulting conclusions show how content marketing will complement social media marketing so that it can be used for the development of small and medium businesses.